Book Review: "International Law: From Theory to Practice" - Tavakol Habibzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book entitled "International Law: From Theory to Practice", written by Dr. Ali Omidi in 2009 and published by Mizan Publications.  According to the author himself, it is written as an educational manual and a workbook for preparation to Master’s Entrance Exam of International Law. Such a purpose of writing a manual has influenced the scientific level of the book in such a way that it is far away from an academic textbook containing the accepted standards and criteria which aim to analyze the documented and scientific way the various fields of international law. In addition to some form of lacunae, this work also suffers from significant deficiencies and deficits, including the lack of use of first-hand resources, the lack of a logical and consistent table of contents, inaccuracies in the titles of some chapters, and quantitative non-proportionality between chapters. It is hoped that the respected author in subsequent publications will pay attention to this assessment in order to elevate the scientific level of the book.